Gnas Inactivation Alters Subcutaneous Tissues in Progression to Heterotopic Ossification - Brewer, Niambi; Fong, John T.; Zhang, Deyu; Ramaswamy, Girish; Shore, Eileen M. (Frontiers in Genetics, 2021)
Heterotopic ossification (HO), the formation of bone outside of the skeleton, occurs in response to severe trauma and in rare genetic diseases such as progressive osseous heteroplasia (POH). In POH, which is caused by inactivation of GNAS, a gene that encodes the alpha stimulatory subunit of G proteins (Gsα), HO typically initiates within subcutaneous soft tissues before progressing to deeper connective tissues. To mimic POH, we used conditional Gnas-null mice which form HO in subcutaneous tissues upon Gnas inactivation. In response to Gnas inactivation, we determined that prior to detection of heterotopic bone, dermal adipose tissue changed dramatically, with progressively decreased adipose tissue volume and increased density of extracellular matrix over time. Upon depletion of the adipose tissue, heterotopic bone progressively formed in those locations. To investigate the potential relevance of the tissue microenvironment for HO formation, we implanted Gnas-null or control mesenchymal progenitor cells into Gnas-null or control host subcutaneous tissues. We found that mutant cells in a Gnas-null tissue environment induced a robust HO response while no HO was detected in control hosts. Additionally, a Gnas-null tissue environment appeared to support the recruitment of control cells to heterotopic bone, although control cell implants were associated with less HO formation compared to mutant cells. Our data support that Gnas inactivation alters the tissue microenvironment to influence mutant and wild-type progenitor cells to contribute to HO formation.